A crooked tree : a novel - Mannion, Una (HarperColllins Publishers, 2021)
It is the early 1980s and fifteen-year-old Libby is obsessed with trees. One night, while driving home, her mother, exhausted and overwhelmed with the fighting in the backseat, pulls over and orders Libby's little sister Ellen to walk home. What none of this family knows as they drive off leaving a twelve-year-old girl on the side of the road five miles from home with darkness closing in, is what will happen next.